Quantitative determination of bond order and lattice distortions in nickel oxide heterostructures by resonant x-ray scattering - Lu, Yi; Haverkort, Maurits W. (Physical review, 2016)
We present a combined study of Ni K-edge resonant x-ray scattering and density functional calculations to probe and distinguish electronically driven ordering and lattice distortions in nickelate heterostructures. We demonstrate that due to the low crystal symmetry, contributions from structural distortions can contribute significantly to the energy-dependent Bragg peak intensities of a bond-ordered NdNiO3 reference film. For a LaNiO3−LaAlO3 superlattice that exhibits magnetic order, we establish a rigorous upper bound on the bond-order parameter. We thus conclusively confirm predictions of a dominant spin density wave order parameter in metallic nickelates with a quasi-two-dimensional electronic structure.
Gesehen am 20.09.2017